Synthesis and characterization of a light-emitting diode from an alternating copolymer - Cho, H.N.; Kim, D.Y.; Kim, Y.C.; Lee, J.Y.; Kim, C.Y. (Society for Information Display, 1998)
Poly(hexyl-fluorenediylvinylene-alt-phenylenevinylene)(PHFPPV) has been synthesized by a Wittig reaction between a fluorene phosphonium salt and terephthalaldehyde. The alternating copolymer was thermally stable to be decomposed at 410°C and soluble in chloroform. The photoluminescence (PL) spectrum is very broad and has shoulders and a bump. The bump at 560 nm disappeared on dilution of the copolymer in chloroform. The EL spectrum is broad, but not as broad as the PL spectrum, and is significantly different from the PL spectrum. The quantum efficiency of the LED was 0.002% with aluminum as a negative electrode, and the turn-on voltage was 20 V.